The Design of EMU - Begg, David (Washington, D.C. : International Monetary Fund, 1997)
Pursuit of price stability may, but need not, exacerbate output fluctuations. This paper discusses the monetary strategy of the European Central Bank, the intermediate targets that this should entail, and implications for accountability, transparency, and reputation. Country-specific shocks will remain but output correlation may not reflect the old pattern of core and peripheral countries. The Stability Pact will force some countries to switch off their automatic stabilizers; others, with fewer fiscal problems, can retain them. Output correlations in EMU may reflect a fiscal core and fiscal periphery. Additional labor market flexibility remains the best solution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet